PENERAPAN PSIKOLOGI ORGANISASI DALAM MANAJEMEN PENDIDIKAN ISLAM - Aidah; Safwandy Nugraha , Mulyawan (Institut Ummul Quro Al-Islami Bogor, 2024)
Effective management is the key for Islamic educational institutions to remain relevant in providing quality education based on Islamic values, while meeting the demands of modern professionalism. The application of organizational psychology in educational management strengthens performance, relationships between staff, and creates a conducive work environment that supports educational goals and character development of students. This study aims to examine how the application of organizational psychology in SD Alfa Centauri is implemented, how it affects management performance and effectiveness, and how this application model can be adapted by other schools. This research uses a qualitative approach. Data collection techniques through interviews and observations. This research succeeded in achieving its goal, which is to identify the application of organizational psychology in SD Alfa Centauri and develop a model that can be adapted by other Islamic educational institutions. This study succeeded in providing a clear picture of how the application of organizational psychology not only supports the welfare of educators, but also improves the quality of school management as a whole.